1981
DOI: 10.1103/physrevlett.47.712
|View full text |Cite
|
Sign up to set email alerts
|

Example of a Negative Effective Poisson's Ratio

Abstract: An effective Poisson's ratio is introduced for anisotropic materials as the negative ratio of transverse and longitudinal strains averaged over all transverse directions. It is shown that for certain orientations of the applied force this effective Poisson's ratio assumes negative values for a-quartz. This implies that such a bar increases its cross section under length extension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…In particular, Poisson's ratio may depend on the choice of the transverse and the longitudinal directions and its definition can be written in the following form [37][38][39]:…”
Section: Elasticity Of Crystalsmentioning
confidence: 99%
“…In particular, Poisson's ratio may depend on the choice of the transverse and the longitudinal directions and its definition can be written in the following form [37][38][39]:…”
Section: Elasticity Of Crystalsmentioning
confidence: 99%
“…Such a property implies that the solid will reduce its cross section upon pressure which defies our everyday experience with solids. Known examples are the Abrikosov lattice in type-II superconductors (D = 2) [101], α-quartz (D = 3) [102], and some foams [103]. Some phases of biopolymers have been shown to exhibit negative Poisson ratio [104].…”
Section: Isotropic Elastic Solidmentioning
confidence: 99%
“…One way to look at this is that by increasing the separation between a disclination and an antidisclination in the solid additional dislocations are introduced given Eq. (102). But in the nematic phase dislocations are completely condensed which implies that dislocations can be pulled out of the condensate 'for free'.…”
mentioning
confidence: 99%
“…The Poisson ratio, namely the negative ratio of the induced lateral strain to the strain parallel to the uniaxial stress, is found to be dependent on the atomic packing density and valance electron density of the material [3,4]. Since the 1980s, it has been reported that materials of reentrant structures can possess an exotic negative Poisson ratio [5][6][7][8]. In practical situations, materials are always in complicated stress states.…”
mentioning
confidence: 99%